BURNOUT AMONG PHYSICAL EDUCATION TEACHERS WORKING IN UPPER PRIMARY AND SECONDARY SCHOOLS OF GOVERNMENT AND PRIVATE SECTOR IN KERALA - Sujith S; T. I. Manoj and Ajith Mohan K.R (International Journal of Physical Education Sports Management and Yogic Sciences, 2014)
The present study examined whether physical education teachers working in government/aided sector and private sector of upper primary and secondary schools experience the same burnout levels. One hundred twenty full-time Kerala physical education teachers from government/aided and private (60 each) of upper primary and secondary schools filled in the “educator’s” version of Maslach Burnout Inventory. Analysis of variance showed that physical education teachers working in the upper primary schools reported significantly and meaningfully higher levels on the core burnout dimension, namely emotional exhaustion” in comparison to their colleagues in the secondary schools. Moreover, the strength of association among the three burnout components was more prominent in private sector than in government sector. The results shows that the education level in which physical education teachers working represents an important job characteristic that influences burnout levels and should be taken into consideration when this syndrome is examined, at least within the Kerala educational system.